Application Of The C4.5 Algorithm To Determining Student's Level Of Understanding - Adeita A. Ndraha; Hardinata, Jaya Tata; Purba, Yuegilion Pranayama (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2022)
This research was conducted to find the rules of the model in measuring the level of students' understanding of the subject. During this pandemic, the learning process is carried out online, so it is difficult to measure students' ability to master the material. This measurement needs to be done so that the evaluation process can be carried out so that the ability of students in one group to achieve the target level of understanding. Currently, evaluation activities have never been carried out because they do not have a model so that evaluation can only be done by giving quizzes and exercises. This problem can be solved by using data mining algorithm C4.5. Attributes used as parameters for assessing student understanding of lessons such as Teaching Method (C1), Learning Media (C2), Communication (C3), Experience (C4), Teaching Materials/Modules/Assignments (C5), Learning Duration (C6). The six attributes are used to find the relationship between each other that influence each other to get the highest root so that a decision tree will be obtained that produces the rules of the relationship between each attribute in determining student understanding of the subject. This rule or rule will be used as the basis for making an information system so that it can be applied to end users, namely schools.